2020
DOI: 10.1007/s13753-020-00315-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Vulnerability Factors and Reported Post-Disaster Needs in the Aftermath of Hurricane Florence

Abstract: This research examines the relationship between social vulnerability factors and reported needs following Hurricane Florence. Weighted least squares regression models were used to identify predictor variables for valid registrations that reported needs pertaining to emergencies, food, and shelter. Data consisted of zip codes in North Carolina and South Carolina that received individual assistance for Hurricane Florence (N = 406). The results suggest that when controlling for event-specific factors and flood mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
6
2
Order By: Relevance
“…Perhaps childcare, eldercare, and other family responsibilities are barriers to middle-aged respondents' ability to evacuate. Households with more dependents and young children encounter more difficulties responding to disaster, in part due to the additional strain on household resources [4,10,31]. In the survey, older adults did not report mobility limitations as a barrier to evacuation, which contradicts prevailing research findings on social vulnerability and disasters [10,31].…”
Section: Age and Vulnerabilitycontrasting
confidence: 62%
See 1 more Smart Citation
“…Perhaps childcare, eldercare, and other family responsibilities are barriers to middle-aged respondents' ability to evacuate. Households with more dependents and young children encounter more difficulties responding to disaster, in part due to the additional strain on household resources [4,10,31]. In the survey, older adults did not report mobility limitations as a barrier to evacuation, which contradicts prevailing research findings on social vulnerability and disasters [10,31].…”
Section: Age and Vulnerabilitycontrasting
confidence: 62%
“…Households with more dependents and young children encounter more difficulties responding to disaster, in part due to the additional strain on household resources [4,10,31]. In the survey, older adults did not report mobility limitations as a barrier to evacuation, which contradicts prevailing research findings on social vulnerability and disasters [10,31]. They indicated that they do not know when to leave or do not have alternative shelter, which supports research showing that populations with a higher proportion of adults over 65 are associated with higher post-disaster shelter needs [31].…”
Section: Age and Vulnerabilitymentioning
confidence: 99%
“…This indicates that the effects of a disaster include more than just physical infrastructure impacts and are linked with social vulnerability as well. Weighing social vulnerability with post-disaster needs of different populations is an ongoing area of research that can help guide prioritization of repairs and resource allocation at a local and regional level (Chakraborty et al 2020;Crowley 2021;Logan and Guikema 2020). Social vulnerability indicators, such as those proposed by Cutter (2003), can help inform this process.…”
Section: -7 Discussion and Conclusionmentioning
confidence: 99%
“…From the SimplyAnalytics database, we utilize the Quality of Life index, the data for which are generated by Easy Analytic Software, Inc. (SimplyAnalytics 2015). As a partner with SimplyAnalytics, Easy Analytic Software, Inc. (EASI) has developed demographic and economic data used by a variety of individuals and organizations in both the private and public sectors, including for use in academic research (e.g., Crowley 2021; Emerson et al, 2001). The EASI Quality of Life variable has been used in scholarly publications by academics in a range of different disciplines (Choudhury, et al, 2021; Clement, et al, 2017; Tsai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%